2021
DOI: 10.3390/biomedicines9070755
|View full text |Cite
|
Sign up to set email alerts
|

Tethered Lipid Membranes as a Nanoscale Arrangement towards Non-Invasive Analysis of Acute Pancreatitis

Abstract: Extracellular heat shock proteins (HSPs) mediate immunological functions and are involved in pathologies such as infection, stress, and cancer. Here, we demonstrated the dependence of an amount of HSP70 and HSP90 in serum vs. severity of acute pancreatitis (AP) on a cohort of 49 patients. Tethered bilayer lipid membranes (tBLMs) have been developed to investigate HSPs’ interactions with tBLMs that can be probed by electrochemical impedance spectroscopy (EIS). The results revealed that HSP70 and HSP90 interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, low serum HSP70 levels are associated with poor prognosis in AP patients (Arriaga-Pizano et al, 2018). Budvytyte et al discussed these two findings above, as they found out the serum HSP90 levels increased linearly with increasing AP severity while the relationship was not linear in the case of HSP70 (Budvytyte et al, 2021). The mechanisms of extracellular HSP in AP are not yet conclusively elucidated, so further investigations are still required.…”
Section: Heat Shock Proteins (Hsps) and Apmentioning
confidence: 99%
“…In addition, low serum HSP70 levels are associated with poor prognosis in AP patients (Arriaga-Pizano et al, 2018). Budvytyte et al discussed these two findings above, as they found out the serum HSP90 levels increased linearly with increasing AP severity while the relationship was not linear in the case of HSP70 (Budvytyte et al, 2021). The mechanisms of extracellular HSP in AP are not yet conclusively elucidated, so further investigations are still required.…”
Section: Heat Shock Proteins (Hsps) and Apmentioning
confidence: 99%